2008
DOI: 10.1186/1755-8794-1-60
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes of patients with familial hypercholesterolemia show alterations in cholesterol metabolism

Abstract: Background: Elevated plasma cholesterol promotes the formation of atherosclerotic lesions in which monocyte-derived lipid-laden macrophages are frequently found. To analyze, if circulating monocytes already show increased lipid content and differences in lipoprotein metabolism, we compared monocytes from patients with Familial Hypercholesterolemia (FH) with those from healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…In circulating monocytes from three out of four patients homozygous for familial hypercholesterolemia, the TRPC3 mRNA was notoriously up-regulated compared with heterozygous or control patients (32). Despite these suggestive data showing a correlation between increased expression levels of TRPC3 and presence of atherosclerosis, whether TRPC3 has an active role in the pathogenesis of the human lesion, remains unknown.…”
Section: Discussionmentioning
confidence: 94%
“…In circulating monocytes from three out of four patients homozygous for familial hypercholesterolemia, the TRPC3 mRNA was notoriously up-regulated compared with heterozygous or control patients (32). Despite these suggestive data showing a correlation between increased expression levels of TRPC3 and presence of atherosclerosis, whether TRPC3 has an active role in the pathogenesis of the human lesion, remains unknown.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have reported that SAA could enhance oxidized LDL-induced foam cell formation, which plays an important role in the pathogenesis of atherosclerosis [37]. Although the epigenetic regulation of this process remains unclear, Jmjd3 expression was increased in patients with familial hypercholesterolemia (FH) compared with healthy individuals [38] (Supplementary Fig. S3A).…”
Section: Resultsmentioning
confidence: 99%
“…Monocytes do express scavenger receptors (SRs) to some degree ( 5-7 ) and are exposed to hypercholesterolemic conditions during disease state. Recent studies in mice and in hypercholesterolemic patients have shown lipid accumulations in blood monocytes (8)(9)(10), but the consequences of cellular lipid accumulation, which have been well characterized in macrophages, are still unclear in monocytes.…”
mentioning
confidence: 99%